Estimation of Prevalence of Hospital-Acquired Blood Infections among Patients Admitted at a Tertiary Hospital in Oman over a Period of Five Years: A Cross-Sectional Study - Marah El-Beeli; Yahya Al-Farsi; Abdullah Balkhair; Zakariya Al-Muharrmi; Mansoor Al-Jabri; Samir Al-Adawi (Interdisciplinary Perspectives on Infectious Diseases)
Background. Data from developed/developed countries have shown that hospital-acquired blood infections (HA-BSIs) are one of the most severe nosocomial infections and constitute 20%–60% of hospitalization-related deaths. Despite the high morbidity and mortality rates and the enormous burden of health care costs associated with HA-BSIs, to our knowledge, there are few published reports on HA-BSI prevalence estimates in Arab countries, including Oman. Objectives. This study aims to explore the HA-BSI prevalence estimates over selected sociodemographic characteristics among admitted patients at a tertiary hospital in Oman over five years of follow-up. The regional variations in Oman were also examined in this study. Methods. This hospital-based cross-sectional study reviewed reports of hospital admissions over 5 years of retrospective follow-ups at a tertiary hospital in Oman. HA-BSI prevalence estimates were calculated over age, gender, governorate, and follow-up time. Results. In total, 1,246 HA-BSI cases were enumerated among a total of 139,683 admissions, yielding an overall HA-BSI prevalence estimate of 8.9 cases per 1000 admissions (95% CI: 8.4, 9.4). HA-BSI prevalence was higher among males compared to females (9.3 vs. 8.5). HA-BSI prevalence started as relatively high in the group aged 15 years or less (10.0; 95% CI 9.0, 11.2) and then declined as age increased from 36 to 45 years (7.0; 95% CI 5.9, 8.3) when it started to increase steadily with increasing age in the group aged 76 or more (9.9; 95% CI 8.1, 12.1). The governorate-specific estimate of HA-BSI prevalence was the highest among admitted patients who resided in Dhofar governorate, while the lowest estimate was reported from the Buraimi governorate (5.3). Conclusion. The study provides supportive evidence for a steady increase in HA-BSI prevalence over age categories and years of follow-up. The study calls for the timely formulation and adoption of national HA-BSI screening and management programs centered on surveillance systems based on real-time analytics and machine learning.